Commands and prohibitions and their implications - Mahazir, Maisarah Nafisa; Md Remali @ Muhd Ramli, Nurul Iwana Izah; Mohd Fahmi, Nurin Fatini Syazani; Ariffin, Nur Atirah Mashitah; Zakaria, Nur Aina Alia (2024)
Slide Presentation: “Commands and prohibitions and their implications”